Ecotherapy – A Forgotten Ecosystem Service: A Review - Summers, James K.; Vivian, Deborah N. (Frontiers in Psychology, 2018)
Natural ecosystems provide important services upon which humans depend. Unfortunately, some people tend to believe that these services are provided by nature for free; therefore, the services have little or no value. One nearly forgotten ecosystem service is ecotherapy – the ability of interaction with nature to enhance healing and growth. While we do not pay for this service, its loss can result in a cost to humans resulting in slower recovery times, greater distress and reduced well-being. Losses in these images of nature can diminish our basic happiness. Little is understood or, at least, appreciated concerning the potential ecotherapy benefits of the natural environment and its ecosystem services. The complex and interactive relationship of ecosystems, their services and human well-being is poorly acknowledged in the broad social, philosophical, psychological and economic well-being literature. In this article, we examine the role of nature and its ecosystem services in ecotherapy and its associated enhancement of recovery from physical and mental illness through a review of studies evaluating this ecosystem service-recovery connection.